Cementoenamel junction: An insight - Kharidi Laxman Vandana; Ryana Kour Haneet (Wolters Kluwer Medknow Publications, 2014)
The location and nature of cemento-enamel junction (CEJ) are more than descriptive terms used simply to describe some aspects of tooth morphology; however, CEJ gains a lot of clinical significance due to various measurements dependent on it. It may be necessary to determine the location and pathological changes occurring at CEJ to make a diagnosis and treat diseases pertaining to epithelial attachment and gingival margin. However, the information related to CEJ is not discussed commonly. Hence, the present review paper provides an insight on CEJ in both primary and permanent dentition.